Fiber-optic sensor cable for simultaneous distributed measurement of multiple physical quantities : doctoral thesis - Bašić, Petar (P. Bašić ; Fakultet elektrotehnike i računarstva, 2019)
Fiber optic sensor cable technology is a relatively new research area that combines a set of scientific and technical disciplines in order to meet distributed sensor systems needs and quality standards. This thesis discusses a particular fiber optic cable design with three tightly encapsulated fibers for multipurpose and multivalent sensing, presently commercialized for temperature, strain and acoustic measurements. Furthermore, it introduces a mechanism for birefringence change as a function of outer perturbations, such as pressure and cable bending, as a new capability and potential feature for future optical sensor products. The concept is based on using cable raw materials (optical fiber, stainless steel strips, matured manufacturing procedures) with standard geometries produced and commercialized in high volumes nowadays. It uses symmetrical elements only and it exploits the geometrical configuration of equilateral triangle with optical fibers in each vertex that are tight buffered within the stainless-steel tube. This results with unsymmetrical loading of the optical fibers when exposed to external hydrostatic pressure thus giving rise to the birefringence change in the optical fibers. In this way the hydrostatic pressure as external mechanical measurand is coupled with optical parameters inside the interior optical fibers hermetically closed inside the stainless-steel tube. The concept was first evaluated with the Finite Element Analysis (FEA) commercial software tool resulted in proving the concept and giving the insight into the magnitude of tube compression.